Hubungan Tingkat Stres dengan Produksi ASI Ibu Postpartum (Nifas) di PMB Soemidjah Ipung Malang - Camelia Rif’a Martha Citraningrum; Jupriyono, Jupriyono; Asworoningrum Yulindahwati (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Breast milk production is a critical concern for postpartum mothers, as inadequate milk supply can lead to the failure of exclusive breastfeeding. This may result in insufficient infant nutrition, while mothers may experience mastitis due to blocked milk ducts. One factor influencing milk production is stress. Maternal stress and anxiety can disrupt lactation by inhibiting milk ejection. This study aims to examine the correlation between stress levels and breast milk production among postpartum mothers at PMB Soemidjah Ipung Malang.  The research employed a correlational analytic design with a cross-sectional approach, involving a population of 31 postpartum mothers who met the inclusion criteria. Total sampling was used, with all 31 respondents included as the sample. Data were collected using standardized questionnaires: the Perceived Stress Scale (PSS-10) and a breast milk production questionnaire. Statistical analysis was conducted using Spearman’s test with a confidence level of ≤ 0.05. The results showed p-values of 0.01 for the relationship between stress levels and milk production (maternal factors) and 0.005 (infant factors), with correlation coefficients of 0.456 and 0.489, indicating a moderate association.  The study rejects the null hypothesis (H0), confirming a significant relationship between stress levels and breast milk production. These findings highlight the importance of addressing excessive stress in postpartum mothers to ensure optimal lactation. Healthcare providers should consider stress management strategies to support breastfeeding success.